Depressive disorders in cardiology practice : Diagnosis and treatment - F. Yu. Kopylov (Klinicist, 2014)
The paper discusses the problems of correct diagnosis and rational pharmacotherapy of depressive disorders in patients with cardiovasculardiseases frequently found by practical cardiologists and therapists.